Penambahan Serbuk Karet SIR.20 Pada Tanah Lempung Sebagai Bahan Inti Bendungan - Ilyas Sadad (Universitas Bandar Lampung, 2012)
Dam is a construction crosses the river to arise up water surface in the reservoir and also retains seepage flow to downstream. In the earth fill dam, the seepage is minimized by the impervious zone. That is usually composed of clay soil fine soil. In this research, natural rubber powder SIR.20 is used to improve the characteristics of impervious zone material i.e.: clay and sand-mo. The tested characteristics of physical and mechanical test by using model at tank permeability. The result show that the addition of rubber powder to clay soil could increase direct shear from 10o at rate 0% to 14o at rate 12,5%, permeability coefficient from 5,97x10-6 cm/sec to 3,23x10-4 cm/sec, seepage flow from 1,581x10-5 cm3/sec to 8,57x10-4 cm3/ sec, and reduce swelling from 16,81% at rate 0% to 7,40% at rate 12,5%. Meanwhile, the addition of rubber powder to sand-mo could increased direct shear from 15o at rate 0% to 28o at rate 12,5%, and reduce swelling from 14,85% at rate 0% to 4,78% at rate 12,5%, permeability coefficient from 3,09x10-5 cm/sec to 8,74x10-6 cm/sec, and seepage flow from 8,17x10-5 cm3/sec to 2,31x10-5 cm3/ sec. Based on the test result, it can be concluded that the addition of rubber powder to sand-mo could improve its impervious. In the contrary, addition of rubber powder to clay soil could worsen its impervious.